Analgesia by telemedically supported paramedics compared with physician‐administered analgesia: A prospective, interventional, multicentre trial. (23rd February 2016) - Brokmann, J.C.; Rossaint, R.; Hirsch, F.; Beckers, S.K.; Czaplik, M.; Chowanetz, M.; Tamm, M.; Bergrath, S.
Abstract: Background: In German emergency medical services (EMS), the analgesia is restricted to physicians. In this prospective, interventional, multicentre trial, complications with and quality of telemedically delegated analgesia were evaluated. Methods: If prehospital analgesia was necessary, five telemedically equipped paramedic ambulances from four different districts could consult a telemedicine centre. Analgesics were delegated based on a predefined algorithm. Telemedically assisted cases were compared with local historical regular EMS missions using matched pairs. The primary outcome was the frequency of therapeutic complications (respiratory/circulatory insufficiency, allergic reactions). Secondary outcomes were quality of analgesia (11‐point numerical rating scale, NRS) and the frequency of nausea/vomiting. Results: Analgesia was necessary in 106 telemedically assisted missions. In 23 cases, the telemedical procedure was used until an EMS physician arrived. Of the remaining 83 cases, 80 could be matched to comparable controls. Complications did not occur in either the study group or the control group (0 vs. 0; p = N/A). Complete NRS documentation was noted in 65/80 (study group) and 32/80 (control group) cases ( p < 0.0001). Adequate initial pain reduction (quality indicator: reduction of NRS ≥ 2 points or NRS < 5 at end of mission) occurred in 61/65 versus 31/32 cases ( p = 1.0); NRS reduction during mission was 3.78 ± 2.0 versus 4.38 ± 2.2 points ( p = 0.0159). Nausea and vomiting occurred with equal frequency in both groups. Conclusions: Telemedical delegation of analgesics to paramedics was safe and led to a pain reduction superior to the published minimum standard in both groups. The documentation quality was better in the telemedicine group. What does this study add?: Little is known about the safety and quality of prehospital analgesia carried out by emergency medical services (EMS). Beside potential quality problems, in some countries meaningful pain reduction is limited by legal regulations that allow only physicians to administer analgesics. This first multicentre prospective trial for telemedically delegated analgesia demonstrates that remote analgesia is possible and safe and retains equivalent analgesic quality compared with that administered by onsite EMS physicians.